Test-Taking Skills and Academic Performance in English of Grade 7 ESL Learners - Abegael Villanueva Acosta; Shienna Marie L. Caparas (Researchparks Publishing, 2026)
This study examines the impact of test-taking skills on the English academic performance of Grade 7 English as a Second Language (ESL) learners in District V of the City Schools Division of Cabuyao. The research evaluates learners’ competencies in reading comprehension, interpreting test instructions, managing time and pacing, and employing analytical reasoning and strategic approaches. A total of 303 learners from three public secondary schools participated. Findings reveal that test-taking skills are moderately developed overall, with strengths in reading comprehension and notable deficiencies in time management. Students grade in the third quarter ranged from satisfactory to very satisfactory, with considerable variation across sections. Correlation analysis identifies a strong relationship between test-taking skills and academic achievement while instructional practices and classroom environment contributed substantially to score variability, underscoring the need for structured strategy and targeted interventions. This study is anchored on theoretical perspectives including the Strategic Self-Regulation (S2R) Model, Cognitive Load Theory, Testing Effect Theory, and Self-Regulated Learning (SRL) Theory. Collectively, these frameworks affirm that comprehension, regulation, and strategic use are critical determinants of academic success in ESL contexts and provide the conceptual foundation for designing interventions that strengthen learners’ test-taking competence.